2008
DOI: 10.1002/ajmg.b.30835
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the 3′ UTR of the serotonin transporter are associated with cognitive flexibility in rhesus macaques

Abstract: The serotonin system is an important neurophysiological mediator of many behavioral phenotypes. Genetic variation within this system is thought to contribute not only to the natural range of behavioral differences, but also to neuropsychiatric pathologies. Cognitive flexibility, the ability to change patterns of response as reward context shifts, is an important trait that underlies many complex social interactions. Environmental manipulations of the serotonin system have been shown to alter performance on tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 74 publications
3
20
0
Order By: Relevance
“…Namely, the SS carriers might have found the mental arithmetic task harder than the SL þ LL carriers resulting in greater reactivity. Indeed, recent studies of animals (Izquierdo et al 2007;Vallender et al 2008) and humans (Fiedorowicz et al 2007;Jollant et al 2007) have shown that the S allele compared to the L allele is associated with reduced higher cognitive function. However, another study has shown no differences for basic intelligence between human 5HTTLPR genotypes (Gotlib et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Namely, the SS carriers might have found the mental arithmetic task harder than the SL þ LL carriers resulting in greater reactivity. Indeed, recent studies of animals (Izquierdo et al 2007;Vallender et al 2008) and humans (Fiedorowicz et al 2007;Jollant et al 2007) have shown that the S allele compared to the L allele is associated with reduced higher cognitive function. However, another study has shown no differences for basic intelligence between human 5HTTLPR genotypes (Gotlib et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Little is known about the mechanisms underlying RI. Vertebrate studies suggest the involvement of serotonin [38,39]; it is unclear whether serotonin plays a role in insect learning ( [40][41][42][43]; but see [44]). Interestingly, PKG is thought to modulate serotonin (5-hydroxytryptamine; 5-HT) transporter activity [43].…”
Section: Discussionmentioning
confidence: 99%
“…Rhesus monkeys with two copies of the short allele of the rhesus 5-HTT (i.e., the 5-HT transporter) gene-linked polymorphic region (rh5-HTTLPR) showed reduced cognitive flexibility on two tasks: object discrimination reversal learning and instrumental extinction (Izquierdo et al 2007). Genetic variation at the 5-HTT 3′ untranslated region, independent of rh5-HTTLPR, also affects performance in object discrimination reversal learning in rhesus monkeys (Vallender et al 2009). …”
Section: Cognitive Flexibility and 5-htmentioning
confidence: 96%
“…Two rhesus monkey studies at least support a role for 5-HT in cognitive flexibility (Izquierdo et al 2007;Vallender et al 2009). In sum, these studies tend to support the hypothesis that 5-HT activates the PFC.…”
Section: Cognitive Flexibility and 5-htmentioning
confidence: 97%